Two new species of Hemiphyllodactylus (Reptilia: Gekkonidae) from Laos - Eliades, Samuel J.; Phimmachak, Somphouthone; Sivongxay, Niane; Siler, Cameron D.; Stuart, Bryan L. (Zootaxa, 2019)
Two new species of the gekkonid lizard genus Hemiphyllodactylus are described based on specimens collected from Champasak Province in southern Laos and Houaphanh Province in northern Laos. Phylogenetic analyses recover H. indosobrinus sp. nov. from Champasak Province as the sister lineage to the Thai endemic H. flaviventris. Hemiphyllodactylus indosobrinus sp. nov. can be diagnosed by having 15 supralabial scales, eight chin scales, 4‑5‑5‑4 subdigital lamellae on Fingers II–V, 4‑5‑5‑5 subdigital lamellae on Toes II–V, and 18 continuous precloacofemoral pores. Phylogenetic analyses recover H. serpispecus sp. nov. from Houaphanh Province to be most closely related to the Vietnamese endemic H. banaensis. Hemiphyllodactylus serpispecus sp. nov. differs from congeners by having seven chin scales; 3‑4‑4‑4 subdigital lamellae on Fingers II–V; 3‑4‑4‑5 subdigital lamellae on Toes II–V; and 11 continuous precloacofemoral pores. The recognition of these two new species doubles the number of Hemiphyllodactylus known from Laos.